The Important Role of Dendritic Cell (DC) in iNKT-Mediated Modulation of NK Cell Function in Chlamydia pneumoniae Lung Infection - Lei Zhao; Xiaoling Gao; Hong Bai; Antony George Joyee; Shuhe Wang; Jie Yang; Weiming Zhao; Xi Yang (Mediators of Inflammation, 2019)
Chlamydia pneumoniae (Cpn) infection causes multiple acute and chronic human diseases. The role of DCs in host defense against Cpn infection has been well documented. The same is true for invariant natural killer T (iNKT) cells and NK cells, but the interaction among cells is largely unknown. In this study, we investigated the influence and mechanism of iNKT cell on the differentiation and function of NK cell in Cpn lung infection and the role played by DCs in this process. We found that expansion of IFN-γ-producing NK cells quickly happened after the infection, but this response was altered in iNKT knockout (KO) mice. The expression of activation markers and the production of IFN-γ by different NK subsets were significantly lower in KO mice than wild-type (WT) mice. Using in vitro DC-NK coculture and in vivo adoptive transfer approaches, we further examined the role of DCs in iNKT-mediated modulation of NK cell function. We found that NK cells expressed lower levels of activation markers and produced less IFN-γ when they were cocultured with DCs from KO mice than WT mice. More importantly, we found that the adoptive transfer of DCs from the KO mice induced less NK cell activation and IFN-γ production. The results provided evidence on the modulating effect of iNKT cell on NK cell function, particularly the critical role of DCs in this modulation process. The finding suggests the complexity of cellular interactions in Cpn lung infection, which should be considered in designing preventive and therapeutic approaches for diseases and infections.